Belarusian State University students’ marriage and family values - Kurilovich, Natalia V. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The article considers the marriage and family values of student youth as an area of interdisciplinary study. It is noted that students’ axiological orientations in the sphere of marriage and family act as a subjective factor in the demographic development of Belarus. From the position of sociological science the content of the concept «marriage and family values» is revealed. The thematic diversity of works, devoted to the study of the value world of modern student youth, is demonstrated. The results of the sociological research «Value orientations and everyday practices of BSU students», conducted in 2024, are represented. It is stated that family is the most important value in the life of young people, studying at the leading university of the country. The respondents’ ideas about marriage union are characterised, and their reproductive attitudes are considered. It describes the attitude of students to non-traditional forms of marriage and such neoliberal attitudes in the marriage and family sphere as сhildfree, non-traditional sexual orientation, gay marriage, abortion and polygamy.
Keywords: family; marriage; marriage and family values; non-traditional forms of marriage; reproductive attitudes; student youth; Belarusian State University; sociological survey